Development Development of Contextual Interactive Multimedia Assisted by Adobe Animate Oriented to Self-Regulated Learning of High School Students on Buffer Solution Material - Ayu Sriwidhia Ningsih; Zurweni Zurweni; Aulia Sanova (Departement of Mathematics Education, 2024)
Education in Indonesia uses the independent curriculum as a tool to achieve goals. Self-regulated learning is the process of creating or monitoring affective and cognitive processes during the completion of academic tasks. One of the important chemical materials to understand is the Buffer Solution material. The contextual approach helps teachers relate the material taught to real-world situations and relate what they know to application in everyday life. In the learning process, the use of interactive media can improve students' understanding of concepts, their achievements, and self-regulated learning abilities. This study aims to determine the effectiveness of the use of contextual interactive multimedia oriented to self-regulated learning of students on buffer solution materials. This study uses a narrative review method by comparing data from several relevant journals. The results of the study show that the use of interactive multimedia has a great effect on self-regulated learning ability. This is proven in previous research that the use of contextual-based interactive multimedia is very practical and fosters interest in the learning process so that it will have an impact on self-regulated learning capabilities. So that buffer solution materials presented with contextual-based interactive multimedia are very influential and can improve self-regulated learning capabilities.